A DETAIL REVIEW ON CONCEPTUAL STUDY OF TWACHA (SKIN) â€“ AYURVEDIC AND MODERN VIEW.: Array - Dr. Shubham S. Jaiswal, (Ayurline: International Journal of Research in Indian Medicine, 2024)
ABSTRACT Introduction The ageless and timeless science of Ayurveda provides us with the tools to achieve and preserve our own ideal health and wellbeing. Throughout the ages, Ayurveda has been transmitted as a comprehensive medical system. Skin is the largest organ of body. With its ability to cover the whole exterior surface of the body, skin is one of the most vital body parts and sensory organs. According to Acharya Sushruta there are five sensory organs i.e. Gyanendriyas. Sparshanendriya is one of them whose adhishthana is Twacha (skin). As we know, skin is the largest sense organ of the body which sense touch, pain, pressure, temperature etc. It is also known as â€œThe First Line of Defenceâ€. Now a days skin diseases are developing rapidly and peoples are more curious for that. Healthy Skin represent and considered as beauty symbol, hence there is need to know more and detail knowledge about skin. Hence the study is done. Aim and objectives - To study concepts of Twacha (Skin) described in various Ayurvedic literatures. Discussion â€“ ayurveda not cure the symptoms but also removed disease from roots, skin diseases are cosmetically, psychologically is more important. This study helped to know about the details about twacha (skin). Keywords â€“ twacha, twak, charma, twaka Utpatti.